2019
DOI: 10.1080/02602938.2018.1524000
|View full text |Cite
|
Sign up to set email alerts
|

Graduates’ evaluations of usefulness of university education, and early career success – a longitudinal study of the transition to working life

Abstract: Graduates' evaluations of usefulness of university education, and early career success -A longitudinal study of the transition to working life AbstractA successful transition from university to working life requires that graduates are able to employ their education and academic competences in real working-life contexts. Our previous research showed that graduates varied in how they were able to reflect on their competences at the time of graduation.The present longitudinal mixed-method study follows the same g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 38 publications
(61 reference statements)
5
49
0
1
Order By: Relevance
“…Most formal learning modules propose a sequence of learning assessment with, in general, suggestions for further learning according to prior assessment results. Graduates, for example, have limited ability to self-assessment [32] therefore they need an employability assessment tool which offer also recommendations according to the type of job profile, like the proposed innovative tool from this study.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Most formal learning modules propose a sequence of learning assessment with, in general, suggestions for further learning according to prior assessment results. Graduates, for example, have limited ability to self-assessment [32] therefore they need an employability assessment tool which offer also recommendations according to the type of job profile, like the proposed innovative tool from this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, studies dealing with informal or non-formal learning have shown a lack of evaluation tools adapted to these types of training situations, particularly in a dynamic dimension over the duration of an integration path (in vocational situations) [34], or, in the case of students, a medium-low development of competencies for employability [3]. A successful transition from university to working life requires that graduates are able to employ their education and academic competences in real working-life contexts [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding transversal employability skills, HEIs must ensure that students are prepared to handle and solve complex problems in an environment of uncertainty [51] and produce employable graduates that contribute to economic growth and sustainable development [52]. Some studies analyze the integration between higher education and job skills and the positive effects that it entails [53,54]. The European Commission [55] explains the connection between sustainable growth, education, and the labor market [56]: it is necessary to improve the performance of education systems to facilitate the entry of young people into the labor market; the acquisition of new skills that empower people and empower their job training and the best adaptation between labor supply and demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other authors [67][68][69][70] research the incorporation of transversal competences applied to the university sector; while other studies analyze the integration between higher education and job skills and the positive effects that it entails [53,54,71]. The Phoenix report of Future Work Skills H2020 [72] proposes the following skills as a basis for achieving success in the workplace: Creating meaning, social intelligence, original and adaptive thought, trans-cultural competence, literacy in new means of communication, transdisciplinary to understand concepts through multiple disciplines, developing a way of thinking in order to attain the desired results, cognitive load management, virtual collaboration as a member of a virtual team, computational thinking for transferring large quantities of data into abstract concepts and to understand data-based reasoning [73].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding transversal employability skills, higher education institutions (HEIs) must ensure that students are prepared to handle and solve complex problems in an environment of uncertainty [45], producing employable graduates that contribute to economic growth and sustainable development [46]. Some studies analyse the integration between higher education and job skills and the positive effects that it entails [47,48]. The European Commission [49] explains the connection between sustainable growth, education and the labour market [50]: it is necessary to improve the performance of education systems to facilitate the entry of young people into the labour market; the acquisition of new skills that empower people and empower their job training and the best adaptation between labour supply and demand.…”
Section: Introductionmentioning
confidence: 99%